2011
DOI: 10.1007/s12562-011-0335-x
|View full text |Cite
|
Sign up to set email alerts
|

Migration history of Sakhalin taimen Hucho perryi captured in the Sea of Okhotsk, northern Japan, using otolith Sr:Ca ratios

Abstract: Sakhalin taimen Hucho perryi populations have decreased drastically to near extinction. It is urgent to establish an effective conservation strategy based on an understanding of the characteristics of migration and habitat use of this species. We examined the migration history of anadromous Sakhalin taimen captured off the Sarufutsu coast, northern Hokkaido, Japan, using otolith Sr:Ca ratios and also examined the relationship between their otolith Sr:Ca ratios during freshwater and seawater residence in a rear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…The taimen examined by Edo et al (2005) were >8 years old at time of capture. In contrast, Suzuki et al (2011) found that some fish migrated to sea before age-3. Arai et al (2004) also examined three juvenile taimen (<13.0 cm fork length) and one adult taimen (70.0 cm fork length) that had not migrated to saltwater based on otolith microchemical profiles.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…The taimen examined by Edo et al (2005) were >8 years old at time of capture. In contrast, Suzuki et al (2011) found that some fish migrated to sea before age-3. Arai et al (2004) also examined three juvenile taimen (<13.0 cm fork length) and one adult taimen (70.0 cm fork length) that had not migrated to saltwater based on otolith microchemical profiles.…”
Section: Introductionmentioning
confidence: 89%
“…The Sakhalin taimen, unlike other taimen species, is generally considered to be anadromous (Arai et al 2004;Edo et al 2005;Suzuki et al 2011). Kawamura et al (1983) described capture of taimen from brackish waters on the eastern shore of Hokkaido Island, Japan.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Otoliths are metabolically inert structures as new mineral material is neither resorbed nor reworked after deposition, and the uptake of elements into the growing structures usually reflects the physical and chemical aquatic environment (Campana et al, 2000). The Sr:Ca ratios of otoliths can be used as natural tags to describe fish movements between freshwater, brackish and seawater habitats (Secor & Rooker, 2000;Suzuki et al, 2011;Mai et al, 2014). Furthermore, for a wide range of salinities and fish species a well-known positive relationship exists between Sr:Ca ratios in the otoliths and the water where fishes live (Kraus & Secor, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, less is known about the habitat and behavioural ecology of P. perryi fry and juveniles. Previous studies have focused on the anadromous form in either Sakhalin or Hokkaido (Arai et al 2004;Edo et al 2005;Honda et al 2010a;Suzuki et al 2011;Zimmerman et al 2011). With the exception of spawning season information, we also know little about adult P. perryi.…”
Section: Introductionmentioning
confidence: 99%